2017
DOI: 10.3390/w9070499
|View full text |Cite
|
Sign up to set email alerts
|

Actual and Reference Evapotranspiration in a Cornfield in the Zhangye Oasis, Northwestern China

Abstract: Evapotranspiration (ET) is an important component of the surface energy balance and water cycle, especially in arid and semiarid regions. The characteristics of the actual evapotranspiration (ET a), which was calculated using the eddy covariance method, and the reference evapotranspiration (ET 0), which was estimated using the Food and Agriculture Organisation (FAO) Penman-Monteith method, were analysed. This work focussed on the seasonal variations in evapotranspiration and crop coefficient (K c) above the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Li et al [70] reported a range from 1.5-6.5 mm day -1 during the growing season of maize in northwest China, while, Chávez et al [71] found values in the range of 2.5-6.5 mm day −1 during the one month SMACEX and SMEX02 campaigns. Tyagi et al [72] observed a slightly larger range of 3-7 mm day −1 during their experiment over Karnal, India for the growing seasons of 1996 and 1997, while Gu et al [73] provided an estimate between 2-4 mm day −1 for the whole maize season of 2008 in the Zhangye Oasis of China. While providing a broad range of crop water estimates for maize under a range of growing conditions, these literature values are consistent with those reported in Figures 6-8.…”
Section: Potential Of Crop Water Use Estimates From Cubesats For Precmentioning
confidence: 90%
“…Li et al [70] reported a range from 1.5-6.5 mm day -1 during the growing season of maize in northwest China, while, Chávez et al [71] found values in the range of 2.5-6.5 mm day −1 during the one month SMACEX and SMEX02 campaigns. Tyagi et al [72] observed a slightly larger range of 3-7 mm day −1 during their experiment over Karnal, India for the growing seasons of 1996 and 1997, while Gu et al [73] provided an estimate between 2-4 mm day −1 for the whole maize season of 2008 in the Zhangye Oasis of China. While providing a broad range of crop water estimates for maize under a range of growing conditions, these literature values are consistent with those reported in Figures 6-8.…”
Section: Potential Of Crop Water Use Estimates From Cubesats For Precmentioning
confidence: 90%
“…They also concluded that ETa depends on local meteorological elements, increasing as temperature, wind speed, and incoming solar radiation increase, and as relative air humidity decreases. Similarly, [14] concluded that ETa is positively correlated with net radiation, wind velocity, air temperature, and specific humidity. Our results show that water restriction only applied in calculating ETo, and not ETa.…”
Section: Eta (C)mentioning
confidence: 95%
“…We validated the ETa estimates from the model using the latent heat flux data, and the soil water content model using the soil water content measurements collected at the site. The flux tower ETa is calculated with the following equation from Gu et al (2017):…”
Section: Model Updatesmentioning
confidence: 99%